TRADISI MANDOA KATOMPAT DAN RATIK TAGAK PADA HARI RAYO ANAM DI JORONG SIKALADI NAGARI PARIANGAN KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Diva Nofia; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Jorong Sikaladi Nagari Pariangan Tanah Datar Regency West Sumatera Province. The purpose of this research is to know the process of the implementation of the tradition of mandoa katunc and tagak rat on rayo anam day, and to know how the impact of the tradition of mandoa katunc and tagak on rayo anam day on the social and economic aspect masyarat Jorong Sikaladi Nagari Pariangan. Purposive Sampling sampling technique because the author has set some criteria subject to be used as a source of information in research that will be done as many as 16 people. The author uses Qualitative methods with data collection techniques such as observation, interview, literature study and documentation. The results found that rayo anam was the same as the grave pilgrimage. On the day of rayo anam there are two traditions of the mandoa katompat (grave pilgrimage) and ratik tagak (dhikr while standing). The process of execution of this tradition can be grouped into three stages of the net phase of the grave, the second stage of implementation and stage after the implementation of eating together. This tradition was held on the eighth day of Shawwal, which coincided on Thursday after performing a six-day fast during the month of Shawwal, which is from the 2nd to the 7th Shawwal. This tradition is carried out in purnam purnam pasukuan by all Jorong Sikaladi community except for traditions of rat tagak which may only be done by men only. The meaning of rayo anam in terms of religion for pilgrimage and mendo'akan soul of the deceased family, increase confidence and increase the faith to Allah SWT, as a field of charity worship, reminiscent of death and as tranquility of the soul for people who carry out the tradition. In terms of culture to establish silaturrahmi, strengthen unity and also unity, as well as the establishment of a sense of togetherness in the principles of mutual life and mutual sharing among peoples. Community response about rayo anam in social aspect that is tied silaturrahmi rope among fellow citizens. In the economic aspect of this tradition has a considerable impact on the outside community but has no impact on the Jorong Sikaladi community itself.The Key word: Implementation, Impact, Mandoa katompat, Ratik Tagak, Rayo Anam